Prostaglandin E(2)-EP2 signaling as a node of chronic inflammation in the colon tumor microenvironment - Aoki, Tomohiro (Inflamm Regen, 2017)
BACKGROUND: Colorectal cancer is the third most common cancer. Involvement of prostaglandin (PG) system in the pathogenesis of colorectal cancer has been suggested from clinical studies demonstrating therapeutic effect of NSAIDs including aspirin or selective COX-2 inhibitors. However, mechanisms on how PG regulates inflammatory responses leading to colorectal cancer development remain obscure. Further, careful attention is needed to use these drugs for a long time because of adverse effects due to non-specific inhibition of physiological PG production in addition to pathological one, making the development of alternatives to aspirin important. Recent studies using mouse model of colitis-associated colon cancer, azoxymethane (AOM)-dextran sodium sulfate (DSS) model, have revealed some of the mechanisms on how PG regulates inflammation in lesions and proposed PG receptor as a therapeutic target. MAIN BODY OF ABSTRACT: Among each PG receptor subtype examined, prostaglandin E receptor 2 (EP2) signaling specifically contributes to colorectal cancer formation and inflammation in lesions of AOM-DSS model. EP2 is expressed in neutrophils, infiltrated major inflammatory cells, and tumor-associated fibroblasts (TAFs) in the tumor stroma of this mouse model and also in clinical specimen from ulcerative colitis-associated colorectal cancer. Bone marrow transfer experiments between wild-type and EP2-deficient mice have confirmed the involvement of EP2 signaling in these two types of cells in the pathogenesis of the disease. EP2 signaling in both types of cells regulates the transition to and maintenance of inflammation in multiple steps to shape the tumor microenvironment which contributes to trigger and promote colorectal cancer. In this process, PGE(2)-EP2 signaling synergizes with TNF-α to amplify TNF-α-induced inflammatory responses, forms a positive feedback loop involving COX-2-PGE(2)-EP2 signaling to exacerbate PG-mediated inflammation once triggered, and alternates active cell populations participating in inflammation through forming self-amplification loop among neutrophils. Thus, EP2 signaling functions as a node of inflammatory responses in the tumor microenvironment. Based on such a notion, EP2 can become a strong candidate for therapeutic target of colorectal cancer treatment. Indeed, in AOM-DSS model, a selective EP2 antagonist, PF-04418948, potently suppresses colorectal tumor formation. SHORT CONCLUSION: PGE(2)-EP2 signaling functions as a node of chronic inflammation which shapes the tumor microenvironment and thus is a strong candidate of target for the chemoprevention of colorectal cancer.